Comparative Cytological Effects of Colchicine, 8-Hydroxyquinoline, and Paradichlorobenzene on Mitotic Activity in Allium sativum Root Meristem Cells - R., Geethanjali; A C, Manjula; T J, Nalini; K Y., Prathibha; Apoorva, Apoorva; Nandini, Nandini (Journal of Neonatal Surgery, 2025)
Allium cepa, a widely used model organism in cytogenetic studies, is ideal for evaluating the effects of chemical agents on mitosis. Allium sativum (garlic), though known for its medicinal value, is less commonly used in such studies. This research focuses on the comparative effects of colchicine, 8-hydroxyquinoline, and paradichlorobenzene—three well-known mitotic inhibitors—on the root meristem cells of Allium sativum. Colchicine is a microtubule-disrupting alkaloid that causes metaphase arrest; 8-hydroxyquinoline acts as a chelating agent that interferes with spindle formation; paradichlorobenzene is an aromatic compound known to induce chromosomal abnormalities. Root tips of Allium sativum were treated with each chemical at standardized concentrations for specific durations, followed by fixation, staining, and microscopic analysis. The mitotic index, frequency of chromosomal aberrations, and phase-specific mitotic abnormalities were recorded and compared. Colchicine treatment led to a significant increase in metaphase frequency due to spindle inhibition, often resulting in c-metaphase configurations. 8-hydroxyquinoline exhibited a marked reduction in the mitotic index and induced metaphase arrest, along with chromosomal stickiness and clumping. Paradichlorobenzene exposure caused prominent chromosomal breaks and fragmentation, along with altered mitotic progression. The results demonstrate the differential impact of these chemicals on cell cycle progression, highlighting their effectiveness and mode of action as mitotic poisons. This study contributes to understanding their cytological effects and potential applications in plant cytogenetics and mutation breeding.